2022
DOI: 10.5424/fs/2022313-18791
|View full text |Cite
|
Sign up to set email alerts
|

Litter decomposition in a remnant of Atlantic Rain Forest and bamboo dominance

Abstract: Aim of study: We compared the decomposition rate of the accumulated litter, the stock, and the return of nutrients to the soil, between an area dominated by bamboos in the understory and an area where this dominance does not occur. Area of study: Fontes do Ipiranga State Park, an Urban Fragment of Atlantic Forest at the Municipality of São Paulo, Southeastern Brazil. Materials and methods: The decomposition rates were measured over one year (0, 3, 6, 9, and 12 months), avoiding litter addition thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Bamboo super‐dominance is a response to different levels of disturbance that changes forest dynamics and structure as well as altering community interactions (Buziquia et al., 2019; Campanello et al., 2007; Rother et al., 2016, 2018). In general, studies have showed that changes in biotic and abiotic conditions after bamboo die‐off (such as decreases in invertebrate abundance, higher light penetration, higher temperatures and less moisture) can boost opportunities for seed overstorey germination and seedling growth (Abe et al., 2005; Austin & Marchesini, 2011; Caccia et al., 2015; Giordano et al., 2009; Takahashi et al., 2007; Vieira et al., 2022). This positively affects tree seedling dynamics and richness and promotes successful forest regeneration and stabilization (Budke et al., 2010; Capellesso et al., 2016, 2022; Marchesini et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bamboo super‐dominance is a response to different levels of disturbance that changes forest dynamics and structure as well as altering community interactions (Buziquia et al., 2019; Campanello et al., 2007; Rother et al., 2016, 2018). In general, studies have showed that changes in biotic and abiotic conditions after bamboo die‐off (such as decreases in invertebrate abundance, higher light penetration, higher temperatures and less moisture) can boost opportunities for seed overstorey germination and seedling growth (Abe et al., 2005; Austin & Marchesini, 2011; Caccia et al., 2015; Giordano et al., 2009; Takahashi et al., 2007; Vieira et al., 2022). This positively affects tree seedling dynamics and richness and promotes successful forest regeneration and stabilization (Budke et al., 2010; Capellesso et al., 2016, 2022; Marchesini et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our study was carried out in the Fontes do Ipiranga State Park (hereafter PEFI), a tropical forest fragment of Atlantic Forest located in southeastern Brazil (23°38′08″–23°40′18″ S and 46°36′48″–46°38′00″ W; 759–837 m a.s.l.). The predominant soil types in the area are Inceptisols and Oxisols (Vieira et al., 2022). The regional climate is classified as Cwa in the Köppen system (1948), with an average annual temperature of 18.7°C and total annual rainfall of 1412.3 mm (data from 1933 to 2017, IAG–Instituto Astronomico e Geofisico, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation